J.R. Dymond and Frank A. MacDougall: Science and Government Policy in Algonquin Provincial Park, 1931-1954 - Killan, Gerald; Warecki, George (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1998)
ABSTRACTBetween 1931 and 1954 Frank MacDougall, forester, superintendent of Algonquin Park (1931-1941) and later Deputy Minister of Lands and Forests, and John R. Dymond, University of Toronto zoologist, together fashioned a framework for formal scientific research in the park. MacDougall's resolve to initiate a multiple use management policy informed by research-based knowledge, and Dymond's passion to protect natural diversity for ecological study, were both shaped by developments in Britain and the United States. Their collaborative efforts resulted in a more protectionist policy for Algonquin including the establishment of fisheries, wildlife and forestry research facilities, the first nature reserves, and an innovative interpretive program—all of which profoundly shaped subsequent policies in other Ontario provincial parks.